The Clinician's Toolkit: Laboratory Tests in the Diagnosis of Childhood Tuberculosis Infection and Disease - Highsmith, Heather Young; Mandalakas, Anna Maria (Journal of Pediatric Infectious Diseases, 2018)
Smear microscopy and culture—the mainstay of tuberculosis (TB) diagnostics for the past century—fail to diagnose the majority of childhood TB cases. Promising new tests are becoming rapidly available, but their utility in childhood TB fails to surpass the accuracy of an astute clinician. In this review, we detail conventional and newer tests available for the diagnosis of TB infection and TB disease and their use in children, as well as potential others in development.
Keywords: Mycobacterium tuberculosis; latent tuberculosis; pulmonary tuberculosis; pediatrics